Calculation of the Static Pressure Rise in the Hydropower Plant Penstock During Emergency Closing of the Flow - Hlbočan Peter; Kiš Roman; Murgašová Marta; Csuka Zoltán; Ďurčanský Peter (MATEC Web of Conferences, 2022)
The paper presents an approach to calculate the static pressure rise upstream of a valve in a pressure penstock of a hydropower plant (HPP), i.e. a valve upstream of a turbine, during an emergency closure of the flow. The calculated value of the pressure rise is applied for the design of the appropriate time of the valve emergency closure in the HPP penstock and for the sizing of the various parts of the HPP (structural and mechanical). The basic theoretical background of the problem, calculation relations, the range of validity of the used calculation relations are explained and then the procedure applied to the solution of a specific task from practice is explained.